2021
DOI: 10.7202/1075673ar
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Discourse Analysis of School-Based Behavioural Policies: Reconceptualizing Understandings of Responses to Student (Mis)Behaviours

Abstract: Students who have been labeled as having “behaviour problems” in the school system have some of the worst academic and social outcomes of any student group. In most Canadian provinces, responses to students who misbehave are legislated through Safe Schools policies intended to guide districts and individual schools in responding to student misbehaviour. In this research project, we conducted a critical discourse analysis of Manitoba’s Safe and Caring Schools documentation in order to analyze the ways in which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In education, provincial governments have always held exclusive decision-making power, while the federal government maintains control over Indigenous education and certain health and social governance policies implemented in schools. This decentralized nature of decision-making has resulted in multiple overlaps of authority and fragmentation of policies (Bakker and Cook, 2011; Colorado and Janzen, 2021). Hueglin (2013) argued that the governance structures of Canada and the EU are similar insofar as policy depends on intergovernmental bargaining and on agreement, rather than solely on constitutional power allocations.…”
Section: The Role Of a Political System In Mlg Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…In education, provincial governments have always held exclusive decision-making power, while the federal government maintains control over Indigenous education and certain health and social governance policies implemented in schools. This decentralized nature of decision-making has resulted in multiple overlaps of authority and fragmentation of policies (Bakker and Cook, 2011; Colorado and Janzen, 2021). Hueglin (2013) argued that the governance structures of Canada and the EU are similar insofar as policy depends on intergovernmental bargaining and on agreement, rather than solely on constitutional power allocations.…”
Section: The Role Of a Political System In Mlg Frameworkmentioning
confidence: 99%
“…Limited shared and coordinated vision for education is characteristic of local-level decision-making as well. Colorado and Janzen (2021: 16) found that provincial documentation published by Manitoba Education showed a “lack of common values and approaches resulting in competing beliefs, fractured purposes, and inconsistent tactics for understanding students and engaging with them.” Public school legislation tends to be province-specific with changes and updates getting tagged onto historical documents in a piecemeal fashion without consideration of broad pedagogical positions. In short, the Canadian federalist system tends to more often be a one-way dispersal of information, rather than the ongoing dialogue that exists in the EU system.…”
Section: The Role Of a Political System In Mlg Frameworkmentioning
confidence: 99%